THE HIGH LEVEL ACCESSION DIALOGUE FOR MACEDONIA: ADVANTAGES AND DISADVANTAGES - Mladen Karadjoski (Journal of Liberty and International Affairs, 2015)
One of the strategic goals for the Republic of Macedonia is membership in the European Union. At the end of 2011, the Commission launched a so-called High Level Accession Dialogue for Macedonia, with a possibility to start the negotiations after the fulfillment of the Dialogue goals and benchmarks. For these reasons, the main goal of this paper will be to give an answer of the dilemma whether the Accession Dialogue for Macedonia is an accelerator of the entrance in the European Union, or is just a sophisticated tool for delay of the start of the negotiations for final accession. The expected results will correspond with the future EU plans for Macedonia, but also for the other Western Balkan countries, i.e. we will try to examine whether these countries have a realistic perspective for entrance in the European Union, or they are just a “declarative décor” for the vocabulary of the Brussels diplomats and member countries representatives. That will help to determine i.e. to try to predict the next steps of these countries, connected with the European integration, regardless of the actual constellation in the European Union concerning the Enlargement policy. The descriptive method, content analyses method, comparative method, but also the inductive and deductive methods will be used in this paper.